2015
DOI: 10.15871/1517-8595/rbpa.v17n3p277-284
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de Utilização de Uva-do-Japão (Hovenia dulcis T.) para Produção de Fermentado Alcoólico

Abstract: Hovenia dulcis T. conhecida como uva-do-japão é uma planta originária do Himalaia, possui frutos saborosos e ricos em açúcares quando maduros. É difundida no sul e no sudeste do Brasil. Há poucos trabalhos científicos explorando tal espécie e não há relatos de seu aproveitamento em produtos alimentícios ou bebidas. Esta pesquisa teve como objetivo a determinação da sua composição centesimal e a produção de fermentado de uva-do-japão. A fruta apresentou elevada quantidade de açúcares (açúcar redutor em glicose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…Japan's grape pseudofruits did not differ statistically in relation to pH, with average values of 5.33. Similar pH values have been reported by Fiorio et al (2015) (5.56) for the pulp of the H. dulcis pseudofruit; a slightly higher value was reported by Picolli and Tessaro (2012) for fresh fruits (5.95). This pH indicates that the pseudofruit from different sources have low acidity.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Japan's grape pseudofruits did not differ statistically in relation to pH, with average values of 5.33. Similar pH values have been reported by Fiorio et al (2015) (5.56) for the pulp of the H. dulcis pseudofruit; a slightly higher value was reported by Picolli and Tessaro (2012) for fresh fruits (5.95). This pH indicates that the pseudofruit from different sources have low acidity.…”
Section: Resultssupporting
confidence: 87%
“…The levels of soluble solids found ranged from 40 g/100 g (SG) to 47.66 g/100 g (BC); statistically different, this value is higher than that found by Picolli and Tessaro (2012) when analyzing the pseudofruits of Campo Bonito (PR), who reported a content of 1.045 g/100 g for the same parameter; Fiorio et al (2015), when analyzing the pseudofruit of Francisco Beltrão (PR) found a content of 25.5 g/100 g; Schaefer et al (2017), when analyzing the same pseudofruit, obtained soluble solids content of 25 g/100 g. Thus, it can be inferred that the pseudofruits from Campos da Vertentes in Minas Gerais are much sweeter than the pseudofruits evaluated in Santa Catarina and Paraná. This high content of ForScience, Formiga, v. 10, n. 2, e01072, jul./dez.…”
Section: Resultsmentioning
confidence: 69%
“…14 The peduncles (pseudofruits) can be consumed in natura or in dehydrated form and are also used for alcoholic fermentation, to produce wine or vinegar. 15,16 According to Bampi et al 13 the peduncles are rich in sugars and have a high content of dietary fiber. In addition, the peduncles are known to be a rich source of antioxidant compounds [17][18][19][20] as well as exhibit pharmacological activities, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Além dos aspectos ecológicos, a espécie apresenta uma multiplicidade de usos, sendo utilizada desde quebra-vento e lenha em propriedades rurais, até na indústria alimentícia, cosmética e farmacêutica (CARVALHO, 1994;SCHUMACHER et al, 2008;SHEN et al, 2012;FIORIO et al, 2015), dessa forma, não é entendida como uma espécie problemática no consenso popular. Esse conjunto todo de características torna Hovenia dulcis uma espécie com alto potencial de invasão e explica o fato de Santa Catarina já ter registro de ocorrência da espécie em pelo menos 42% dos seus municípios.…”
Section: Resultsunclassified